Six Clinical Predictors for Intractable Childhood Epilepsy - Senem Ayça; Ramazan Deniz Oral; Pınar Erbay Dündar; Muzaffer Polat (Galenos Yayinevi, 2019)
Aim:This study aimed to determine the significance of six clinical predictors associated with medically intractable childhood epilepsy.Materials and Methods:A retrospective cohort study was conducted. A total of 241 children with diagnosed epilepsy were recruited and divided into two groups: 61 patients with intractable epilepsy, and the other 180 patients who responded well to antiepileptic drugs. We investigated seizure semiology, etiology of epileptic encephalopathy, EEG abnormalities and defined the odds ratios (ORs) of predictor factors for intractable childhood epilepsy; age of seizure onset, asphyxia, neonatal intensive care unit (NICU) history, consanguineous marriage, abnormal neuro-imaging, neuropathologic exam, prematurity, parents' seizure history.Results:According to logistic regression analysis, the major risk factors for intractable childhood epilepsy are (1) neuropathologic examination p=0.000, OR= 58.28 CI= 23.95-141.63; (2) abnormal neuro-imaging p=0.000, OR= 37.55 CI= 16.41-85.94 (3) age of seizure onset p=0.001, OR= 9.43 confidence interval (CI): 3.66-24.3 (4) asphyxia p=0.001 OR= 4.16 CI= 1.75-9.87 (5) consanguineous marriage p=0.001 OR= 3.02 CI= 1.53-5.97 (6) NICU history p=0.003 OR= 2.59 CI= 1.38-4.87 (95% CI).Conclusion:The presented six predictors can be used to determine the medical intractability in children with epilepsy in order to provide early alternative treatment protocols for better seizure control.